Owners of Learning : The Nyae Nyae Village Schools over Twenty-Five Years - Hays, Jennifer (Basel Namibia studies series, 2016)
This book describes the Nyae Nyae Village Schools, an innovative and unique mother-tongue education initiative set in north-eastern Namibia. Inspired by the optimism of Independence, the project was designed in close consultation with the Ju'hoansi community in the early 1990s. Drawing upon their traditional knowledge transmission strategies, and initiated in a supportive political environment, the project exemplified 'best practice.' During the following two decades, the Village Schools have transitioned from a donor-supported 'project' to government schools, and have received much attention and support from donors, civil society organisations, researchers, and others.However, the students still do not seem to succeed in the mainstream schools. Why is this? Based on long-term field-work in the region, including interviews with Nyae Nyae residents over several years and work with involved organisations, the book addresses this question. Contextualising the Village Schools within post-Independence Namibia, southern African history and the global indigenous rights movement, it examines the enormous paradoxes that schooling presents for the Nyae Nyae community. 'Owners of Learning' is the English translation of the Ju'hoansi word for 'teacher' and it serves to highlight a fundamental question - to whom does education belong?"